Determinação Eletroanalítica de Tiramina em amostras de Vinho tinto utilizando Eletrodos de baixo custo - Silva, Amanda Gonçalves da (2020)
Red wine is a drink obtained from the fermentation of grape must, in which the main stages of manufacture consist of maceration, alcoholic and malolactic fermentations. Tyramine is a biogenic amine that can be naturally present or formed during winemaking, which can have toxic and pharmacological effects on the body. Due to the importance of health, the number of countries that establish maximum limits for the tyramine content in food is increasing, being important the development of fast and low cost methodologies for the quantification of tyramine. Therefore, the objectives of the study were to develop an electroanalytical sensor using disposable and inexpensive pencil’s graphite carbon electrodes (PGCE) for determining tyramine in commercial red wine samples and during fermentation of Vitis Vinifera grapes, using Differential pulse voltammetry (DPV) and Squarewave voltammetry (SWV). The best experimental conditions were defined and the parameters of each technique were chosen, according to the greater sensitivity and selectivity of tyramine detection response. In addition, studies were carried out on the oxidation mechanism of tyramine with the PGCE. Analytical curves for tyramine oxidation using DPV and SWV were made, analytically validated in relation to linearity, linear range, limit of detection (LoD) and limit of quantification (LoQ), precision, accuracy, robustness and specificity. The study of the tyramine oxidation reaction mechanism with the PGCE proved to be irreversible, adsorptive and involving the exchange of 3 electrons and 3 protons. The best experimental and voltammetric conditions were obtained using the 0.1 mol L-1 Phosphate-buffered saline (PBS), pH 7, for the DPV the amplitude was 50 mV and the scan rate was 16 mV s-1 and in the SWV method the amplitude was 50 mV and the scan rate was 16,14 mV s-1. Based on these conditions, the linear ranges obtained for VPD and VOQ were from 0.6 to 200 μmol L-1 (r2 = 0,9985) and 0.6 to 1000 μmol L-1 (r2 = 0,9969), LoD of 0.52 and 0.77 μmol L-1 and LoQ of 1.74 and 2.36 μmol L-1, respectively. In the analytical validation there was no significant difference between responses in the study of precision, robustness (except for temperature) and specificity (except for gallic acid), the relative standard deviation (RSD) were mostly less than 5%, with low confidence interval (CI) was 95%. The tyramine recoveries in commercial red wine samples varied between 94.4 ± 7.6 and 106.0 ± 2.4% with relative error (% BIAS) ≤ 6% and during vinification they varied 89.2 ± 1.2 to 109.2 ± 7.6% with (% BIAS) ≤ 10.8%. During the vinification it was also noted an increasing trend of tyramine concentration during the fermentation process made with Syrah grapes. Throughout the 4 fermentations, the consumption of sugars and formation of ethanol and glycerol were observed in varying amounts depending on the grape and its geographical location. According to the results, it can be concluded that the methodologies developed combined with the use of PGCE is a simple and fast alternative for the determination of tyramine in wines, in view of the use of disposable materials, with low cost and high reproducibility.